CloudPresence: An Innovative Mobile-Based Teacher Attendance Information System with Firebase Integration - David Maulana Putra Pradana; Afwan Anggara (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
In a dynamic digital era, the efficiency of education management is crucial. This research presents “CloudPresence,” an innovative mobile-based teacher attendance information system that integrates Firebase cloud storage technology and location-based attendance features for SMKN 1 Jatiroto. This system is designed to overcome the limitations of conventional attendance systems, improve accuracy, and ensure the physical presence of teachers at school. The methodology includes requirements analysis, system design with UML, and implementation using mobile technology, Firebase, and location services. Results show significant improvements in attendance accuracy, data management efficiency, and attendance process integrity through location verification. The system offers a comprehensive solution with enhanced data security and real-time accessibility. In conclusion, CloudPresence has the potential to transform school management, drive administrative efficiency, and increase accountability in the education system at SMKN 1 Jatiroto.